Improvement of oral health knowledge in a group of visually impaired students - ERÇALIK YALÇINKAYA, ŞEBNEM (Quintessence Publishing Co., Ltd, 2006)
Purpose: The aim of this study was to evaluate the effectiveness of a repeated oral health education programme on oral health knowledge and hygiene of visually impaired students. Materials and Methods: The study was conducted at one of the two visually impaired boarding schools of Istanbul, Turkey. The number of subjects was 65, comprising 28 totally and 37 partially visually impaired students between 7 and 17 years of age. A 24-item verbal questionnaire was developed to record their general health, impairment, the socio-economic profile and education level of their parents, oral health knowledge, sources of information about oral health, awareness of sugar intake/ caries risk, frequency of dental check-ups and oral hygiene habits, as well as any difficulties they experienced thereby. They were given individual training on oral care three times with two-month intervals within the nine-month framework of the programme. To measure the oral hygiene status, plaque index (PI) and gingival index (GI) scores were recorded of all teeth at four sites throughout the sessions. After completion of the programme, the oral health knowledge of the students was evaluated using the same questionnaire to determine the effectiveness of the programme. Results: Statistically significant improvements were found at the level of oral health knowledge and oral hygiene status both in totally and partially visually impaired students at the end of the study (p < 0.001) as compared with at the beginning. No significant difference was found between the knowledge of totally visually impaired and partially visually impaired students. Conclusion: It was concluded that with an appropriate programme, the oral health knowledge of visually impaired students could be improved. This programme, if conducted on a one-to-one basis, ensures clinical and statistical significance. © quintessenz.
Keywords: Education; Oral health; Visual impairment